From passion to practice: Clinician teachers’ insights on family medicine obstetrical care - Kolker, Sabrina; Biringer, Anne; Nyhof-Young, Joyce; Whitehead, Cynthia; Kukan, Sahana; Bytautas, Jessica; Carroll, June (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Background: Declining numbers of family physicians (FPs) provide obstetrical care - an essential service. Exploring reasons why current family medicine obstetrics (FM-OB) clinician teachers chose this field and what motivates them to continue may inform retention strategies and inspire future family medicine learners. Our objective was to explore perspectives of academic FPs who practice FM-OB with the goal of informing recruitment of future FM-OB practitioners and retention of those currently practicing FM-OB.Methods: Academic FP clinician teachers from three urban multidisciplinary Canadian centers who currently practice FM-OB and deliver at one hospital participated in 60 minute, semi-structured interviews. Questions explored participant experiences providing FM-OB care. Interviews were audio-recorded, transcribed and analyzed using a constant comparison method of descriptive thematic analysis.Results: There were 10 participants. The data revealed an overarching theme highlighting three key influces on the decision to start and continue practicing FM-OB: 1) Individual; 2) Interpersonal, and 3) Systemic influences. Early exposure to positive feedback, hands-on skills, and role models shaped their decisions to start. The joy derived from this work, mentoring, patient relationships, and a supportive environment fueled their commitment to continue practicing.Conclusion: This study highlights the importance of early exposure, effective role models, and supportive systemic factors in encouraging trainees to practice FM-OB and retaining FPs in this field. By also identifying the sources of joy in FM-OB and promoting work-life balance, these findings can help inform programs to retain FM-OB providers and inspire future family medicine learners.